Continuidade do cuidado ao pré-termo após a alta hospitalar : perspectiva de profissionais da estratégia saúde da família - Tanaka, Mariana Camargo (2022)
The neonatal care offered by the entire health care network should promote adequate support to those discharged from Neonatal Intensive Care Units and their families, given that the care received after discharge is crucial for maintaining the health of newborns. preterm. In this sense, primary care occupies an important place in the health care network, as it guides the continuity of care for preterm infants and their families and intermediates access to other services. This study aims to understand how the continuity of care for preterm infants discharged from neonatal intensive care units occurs from the perspective of professionals from the Family Health Strategy (ESF). This is an exploratory descriptive study with a qualitative approach, based on the conceptual perspective of continuity of care proposed by Haggerty et al., (2003), and developed in four family health units in the city of Cuiabá, Mato Grosso. Sixteen professionals from the family health teams who work in the four macro-regions participated in the research, including one professional from each selected team (doctor, nurse, nursing technician and community health agent). For data collection, semi-structured interviews were carried out, audio-recorded and transcribed and later submitted to thematic content analysis. This study was approved by the Research Ethics Committee under opinion number 2,788,928. The ethical precepts provided for in Resolution No. 466/2012 of the National Health Council were met at all stages of this investigation. The targeted analysis allowed us to reveal the way in which the professionals of the family health strategy organize, plan and execute their activities to accompany the preterm child after discharge from the neonatal unit, the difficulties faced and the practices that contribute to the effectiveness of the continuity of care. care for these children and their families. From this analysis, three categories and five thematic subcategories emerged: 1. Organization of the FHS to assist the family members of preterm NBs and the performance of each team member; 2. Weaknesses in the managerial, relational and informational dimensions of continuity of care for preterm infants discharged from the Neonatal ICU; 2.1. Challenges for care in the unit and for referral to specialized services; 2.2. Fragile interactions between the preterm's family and professionals; 2.3. Information: essential aspect for the connection between health professionals and the family of the preterm NB and 3. Potentialities for the effectiveness of the dimensions of continuity of care and the direct influence on the assistance to the family members of preterm NB discharged from the Neonatal ICU; 3.1 Home visits as a tool to bring preterm infants and their families closer; 3.2. Meeting the needs of the preterm family. The professionals explain how the continuity of care for preterm infants discharged from the Neonatal ICU occurs and it is evident that, even though they recognize the limitations, and the health care network, even so, they seek to insert it within the precepts of longitudinality exercised. for family health, despite the lack of training and knowledge about care for this population, they recognize the need to improve and improve the care provided to these children and their families.